Tailored Crystallization Dynamics for Efficient and Stable DMSO‐Free Tin Perovskite Solar Cells - Shengnan Zuo; Alexander Tarasov; Lennart Frohloff; Karunanantharajah Prashanthan; Florian Ruske; Mailis Lounasvuori; Chiara Frasca; André Dallmann; Fengshuo Zu; Florian Mathies; Florian Scheler; Noor Titan Putri Hartono; et al. (Advanced Science)
Abstract Tin perovskite solar cells are emerging as a sustainable lead‐free alternative in thin film photovoltaics. DMSO‐free processed tin perovskites are gaining interest due to the detrimental effects of DMSO on tin oxidation. However, replacing DMSO with other solvents remains challenging due to the accelerated crystallization dynamics in non‐DMSO systems. In this study, the crystallization process in a DMSO‐free solvent system is regulated by managing the transition from the sol‐gel phase to the solid film. Specifically, piperazine dihydriodide (PDAI) and 4‐tert‐butylpyridine (tBP) are utilized to coordinately tune the colloidal chemistry through forming large pre‐nucleation clusters in perovskite ink, further, facilitating the film formation process. By combining tBP and PDAI, a controllable crystallization rate is achieved as evidenced by in situ photoluminescence (PL) measurement during spin‐coating. As a result, tin perovskite films show high crystallinity and improved microstructure. Devices treated with tBP+PDAI exhibit a champion power conversion efficiency of 7.8% and excellent stability without observable degradation for over 3000 h stored in the N2 glovebox. These findings advance understanding and managing crystallization in DMSO‐free solvents processed tin perovskite solar cells.